PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP PRESTASI BELAJAR IPA SISWA KELAS V SD NEGERI GEDONGTENGEN YOGYAKARTA TAHUN AJARAN 2016/2017 - Anisa Eka Pratiwi; Yuli Prihatni (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: This study descriptively aims to know the category of achievement of science subject by using cooperative learning model byÂ teams games tournamentÂ type andÂ conventionalÂ model. Comparatively to know the difference of learning achievement of science subjectÂ byÂ using cooperative learning model byÂ teamsÂ gamesÂ tournamentÂ typeÂ andÂ conventionalÂ model.Â TheÂ typeÂ ofÂ thisÂ studyÂ wasÂ quasi experiment. Data collection techniques used test and documentation. Data analysis techniques used descriptive analysis and hypothesis testing by using t test that was started by homogeneity variant test and normality test. This study shows that the scoreÂ ð‘¡hitungÂ =Â 3,665Â and the score of p = 0,001. Thus,Â itÂ can Â concludeÂ thatÂ thereÂ wasÂ significantÂ differenceÂ ofÂ learningÂ achievementÂ science.Â The average score of learning achievement science that using cooperative learning model by teams games tournamentÂ typeÂ wasÂ higherÂ thanÂ conventionalÂ model.Â It Â meansÂ thatÂ thereÂ areÂ influencesÂ of cooperative learning model by teams games tournament type toward learning achievement science.